Efficient Piezoelectric Energy Harvesting from a Discrete Hybrid Bismuth Bromide Ferroelectric Templated by Phosphonium Cation. Issue 33 (28th April 2022) - Deswal, Swati; Panday, Rishukumar; Naphade, Dipti R.; Dixit, Prashant; Praveenkumar, Balu; Zaręba, Jan K.; Anthopoulos, Thomas D.; Ogale, Satishchandra; Boomishankar, Ramamoorthy
Abstract: Bismuth containing hybrid molecular ferroelectrics are receiving tremendous attention in recent years owing to their stable and non‐toxic composition. However, these perovskite‐like structures are primarily limited to ammonium cations. Herein, we report a new phosphonium based discrete perovskite‐like hybrid ferroelectric with a formula [Me(Ph)3 P]3 [Bi2 Br9 ] (MTPBB ) and its mechanical energy harvesting capability. The Polarization‐Electric field ( P‐E ) measurements resulted in a well‐defined ferroelectric hysteresis loop with a remnant polarization value of 2.1 μC cm −2 . Piezoresponse force microscopy experiments enabled visualization of the ferroelectric domain structure and evaluation of the piezoelectric strain coefficient ( d 33 ) for an MTPBB single crystal and thin film sample. Furthermore, flexible devices incorporating MTPBB in polydimethylsiloxane (PDMS) matrix at various concentrations were fabricated and explored for their mechanical energy harvesting properties. The champion device with 20 wt % of MTPBB in PDMS rendered a maximum peak‐to‐peak open‐circuit voltage of 22.9 V and a maximum power density of 7 μW cm −2 at an optimal load of 4 MΩ. Moreover, the potential of MTPBB ‐based devices in low power electronics was demonstrated by storing the harvested energy in various electrolytic capacitors. Abstract : Phosphonium perovskitoid harvesters : A hybrid bismuth halide salt, [Me(Ph)3 P]3 [Bi2 Br9 ], stabilized by phosphonium cations was synthesized and shown to exhibit ferroelectric polarization as determined by P−E loop and piezoresponse force microscopy measurements. Flexible composite devices of it with polydimethylsiloxane were fabricated and utilized as piezoelectric nanogenerators with high output voltage and power density values. The obtained voltages were further employed for capacitor charging applications.